2020
DOI: 10.1177/2379298120943203
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly Film Festival: Teaching Transformational Leadership

Abstract: This article outlines an active learning exercise that gives students the opportunity to learn and apply the behaviors of transformational leadership theory. Students watch a brief, prerecorded “before” video depicting transactional manager–employee interactions. Students then revise the script so that the manager exhibits the four I’s of transformational leadership—inspirational motivation, individualized consideration, idealized influence, and intellectual stimulation—and act out the new script in a student-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The students found it easier to learn about the application of theoretical concepts through films, journal articles, and case studies. Capitano et al. (2022) and Desai et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The students found it easier to learn about the application of theoretical concepts through films, journal articles, and case studies. Capitano et al. (2022) and Desai et al.…”
Section: Introductionmentioning
confidence: 99%
“…The students found it easier to learn about the application of theoretical concepts through films, journal articles, and case studies. Capitano et al (2022) and Desai et al (2018) described the process of using films to teach cross-cultural management in a flipped classroom setting. Aoki and dos Santos (2020) found that the use of films in teaching leadership in organizations was valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Business schools do this in a number of ways, whether it be full courses devoted to leadership, units in courses such as introductory management or organizational behavior, team projects, or in extracurricular activities. Management Teaching Review has published a number of exercises and articles related to leadership across a range of aspects of the topic, including defining what a leader is (Polin, 2019), preparing to be a leader (Tyran, 2017), how leaders differ (Stratton et al, 2022), and bread and butter concepts like transformational leadership (Capitano et al, 2022).…”
mentioning
confidence: 99%